Efficacy of Prophylactic Low-Dose Ketamine Versus Tramadol for Prevention of Shivering During Spinal Anesthesia - Ashfaq, Muhammed; Qadri, Anjum Anwar; Nigar, Falaq; ., Shabana; Hanif, Ayesha; Aziz, Iram (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the efficacy of prophylactic low-dose Ketamine versus Tramadol for prevention of shivering during spinal anesthesia in patients undergoing lower abdominal surgeries.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Anesthesiology, Combined Military Hospital, Rawalpindi, Pakistan, from Sep 18 to Mar 19.Methodology: There were 86 patients of both genders between the ages of 18 and 50 years, having any type of abdominal surgery under spinal anaesthesia. Patients with coagulopathy, Ketamine allergies, pregnancy, and obesity were excluded. Five minutes after administration of drugs, patients in group A received injections of 0.05 mg/kg of Ketamine, while patients in group B received injections of 1 mg/kg of Tramadol after giving spinal anaesthesia. Using the Crossley and Mahajan scale, the degree of shivering was noted down during the operation and up to 30 minutes after surgery at intervals of 15 minutes.Results: The mean age of patients in group A was 32.35±9.46 years, while the mean age of patients in group B was 31.35±8.84 years. Out of total sample of 86 patients, 57(66.28%) were male while 29(33.78%) were female. After undergoing lower abdominal surgeries under spinal anaesthesia, 34 patients (79.07%) who were given prophylactic low-dose Ketamine reported no post-operative shivering, compared to 21 patients (48.84%) who were given Tramadol (p=0.001).Conclusion: This study concluded that spinal anaesthesia with Ketamine reduces postoperative shivering in individuals undergoing lower abdomen surgery compared to Tramadol.